The Effect of Promotion and Price on Financing Decisions for the Solusi Emas Hijrah (SOLEH) Product at Bank Muamalat Madiun Branch Office - Annisa Rohmatul Hidayah; Near Anggreini Hesti Noviana (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study examines the effect of promotion and price on financing decisions for the Solusi Emas Hijrah (SOLEH) product at Bank Muamalat Madiun. Research Methods: A quantitative associative approach was used. Data were collected from 76 respondents using purposive sampling and analyzed with multiple linear regression using SPSS 22. Results: Promotion has a positive and significant effect on financing decisions, while price has a positive but not significant effect. Simultaneously, both variables significantly influence financing decisions, with promotion as the most dominant factor. Conclusion: Promotion and price affect financing decisions, with promotion being more influential. The bank is advised to strengthen promotion strategies while maintaining competitive pricing.